Using Thomas Model to Evaluate Dye Removal from Aqueous Solutions in Fixed-bed Columns of Activated Carbon - Mahdi Hadi (آب و فاضلاب, 2011)
For the purposes of this study, activated carbon was derived from pine-cone by a chemical-thermal process. Initially, its chemical and physical properties were determined before it was used for the removal of Acid Black 1 and Acid Blue 113 dyes. A batch sorption study was carried out in order to obtain the optimum isotherm model. The monolayer maximum saturation capacities of AB1 and AB113 dyes based on Langmuir isotherm model were determined to be 458 mg dye/g carbon and 286 mg dye/g carbon, respectively. Adsorption of dyes was also studied in a continuous-flow state using a fixed-bed column of activated carbon. The effects of operating variables such as flow rate, bed depth, and dye concentration on the column operation were studied. Data confirmed that the breakthrough curves depended on flow rate, bed depth, and initial dye concentration. Column behavior was investigated using Thomas Model and model parameters were determined by a non-linear regression method. The Langmuir and Freundlich isotherm models were used to fit the experimental data. The best fit of the adsorption isotherm data was obtained using the Langmuir model for both dyes. The results showed that Thomas Model was suitable for the description of breakthrough curves under the experimental condition. The column adsorption capacity was also compared with equilibrium adsorption capacities for each dye.